Bimbingan Konseling Dengan Teknik Problem Solving untuk Membangun Mental Health pada Anak Berhadapan dengan Hukum di Sentra Paramita Mataram - Liza Usmiya (Institut Agama Islam (IAI) Nurul Hakim, 2024)
This research focuses on problems that many children in conflict with the law (ABH) were experiencing mental health problems caused by the various problems they were facing. This research aims to find out the causes of mental health disorders, and to find out the efforts of social workers to overcome mental health disorders and to find out what solutions to overcome the causes of mental health disorders. The subjects in this research were Children in Conflict with the Law (ABH). The method used in this research is a qualitative method with a case study approach. The findings of this research: Children in conflict with the law can experience mental health problems caused by several factors including: inadequate family factors (broken homes), social environment factors, and lack of education. These factors are ultimately the cause of mental health disorders for Children in Conflict with the Law (ABH) at the Mataram Paramita Center. So the conclusion is that for the psychological recovery process of victims of sexual violence and perpetrators of criminal acts, researchers carry out a mentoring process and a counseling process where later in the process the researcher uses problem solving techniques to solve the problems experienced by victims, so that later victims can solve their own problems independently and Later the victim will be able to appreciate himself more (self-esteem).